2017
DOI: 10.1111/gcb.13971
|View full text |Cite
|
Sign up to set email alerts
|

Elevated carbon dioxide and warming impact silicon and phenolic‐based defences differently in native and exotic grasses

Abstract: Global climate change may increase invasions of exotic plant species by directly promoting the success of invasive/exotic species or by reducing the competitive abilities of native species. Changes in plant chemistry, leading to altered susceptibility to stress, could mediate these effects. Grasses are hyper-accumulators of silicon, which play a crucial function in the alleviation of diverse biotic and abiotic stresses. It is unknown how predicted increases in atmospheric carbon dioxide (CO ) and air temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
73
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 77 publications
(123 reference statements)
8
73
2
Order By: Relevance
“…Phalaris aquatica originated in Southern Europe and the Caucasus and while now naturalized, it is exotic to Australia (Popay, ). The observed declines in Si at warmer temperatures observed in the present study are therefore consistent with patterns for exotic species tested by Johnson and Hartley (). We should caution, however, that comparatively few grass species have been investigated in terms of global warming and Si uptake, and most of these (like the current study) were conducted over relatively short time periods.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Phalaris aquatica originated in Southern Europe and the Caucasus and while now naturalized, it is exotic to Australia (Popay, ). The observed declines in Si at warmer temperatures observed in the present study are therefore consistent with patterns for exotic species tested by Johnson and Hartley (). We should caution, however, that comparatively few grass species have been investigated in terms of global warming and Si uptake, and most of these (like the current study) were conducted over relatively short time periods.…”
Section: Discussionsupporting
confidence: 93%
“…In a glasshouse study using eight grass species, elevated temperatures were reported not to affect Si concentrations overall, but some species showed significant responses (Johnson & Hartley, ). In particular, grass species native to Australia contained higher concentrations of Si, which rose in response to warmer conditions ( c .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing number of studies published during recent decades has shown that silicon increases the transcription levels of genes related to plant defense and the activities of enzymes involved in the biosynthesis of phenolic compounds . However, these results contrast with those of Coskun et al , which suggested that, in the absence of stress, silicon supplementation has little or no effect, those of Cooke and Leishman, and those of Johnson and Hartley, who mentioned that foliar silicon concentration was significantly negatively correlated with total phenols.…”
Section: Discussionmentioning
confidence: 87%